SYNCRETISM AND COMMUNICATION - Ştefan VLaDUŢESCU (Social Sciences and Education Research Review)
The present study investigates the idea of communicative syncretism, from a textual and ideational point of view. Philosophical discourse and literary discourse are taken as comparative elements. It starts from texts by Plato and Aristotle and leads to the research of texts by Friedrich Wilhelm Nietzsche, Martin Heidegger, Jacques Derrida, Constantina Noica. The conclusion is reached that philosophy is a textual and ideational consequence of literature and that, reciprocally, later the philosophical sometimes strongly impregnated literature.